Charlotte's web [videorecording (DVD)] - Kerner, Jordan; Hamner, Earl, Jr; Grant, Susannah; Kirkpatrick, Karey; Winick, Gary, 1961-2011; Shepard, Sam, 1943-2017; Fanning, Dakota, 1994-; Anderson, Kevin, 1960-; Davis, Essie; Corbett, Louis; Hogan, Siobhan Fallon; Basaraba, Gary; et al. (Paramount Home Entertainment, 2007)
Fern is a young farm girl who rescues Wilbur, the runt of the litter. Wilbur the pig is saved from certain death and Fern visits him every day at her Uncle Homer's farm. But it's Wilbur's friendship with Charlotte the spider that ultimately saves him from the "smoke house." Charlotte's talent for weaving praiseworthy words about Wilbur into her web turns the Zuckerman farm into a tourist attraction.